FACTORS ASSOCIATED WITH THE DEPRESSION, ANXIETY AND STRESS AMONG HIGH MEDICAL SCHOOL OF PROFESSIONAL STUDIES STUDENTS - Radovanović, Drakče (Medicinski časopis, 2017)
The objective of this research was to examine which factors were related to depression, anxiety and stress among nurses/technicians, professional studies students. A cross-sectional study was conducted among students of the High Medical School of Professional Studies in Belgrade. The sample consisted of 535 students of all three years, between 18 and 56 years of age. Depression, Anxiety and Stress Scale (DASS – 42) was used in the research, as well as a questionnaire on personal information which included data on personal impression regarding the importance of exam marks and the feeling of satisfaction with the self as a student. The results of the study showed that 13.6% of the examined student population had symptoms of depression, 25.6% had symptoms of anxiety and 26% had symptoms of stress, which were varying from mild to extremely showing. Average values for all three inspected scales (depression, anxiety, stress) were statistically significantly different depending on the gender of the participants (p = 0.020; p = 0.001; p = 0.001), employment status (p = 0.007; p = 0.020; p = 0.005), total years of service (p = 0.049; p = 0.051; p = 0.017) and feeling of satisfaction with the self as a student (p = 0.000; p = 0.021; p = 0.004). There was statistically significant difference in average values of the stress scale with respect to the motive to enroll the school (F = 6.445; p < 0.05). Average values of the stress scale were the highest with the participants whose motive was to secure a work position and the lowest with the participants whose motive was promotion in their profession. The results of the research point out the importance of early detection of mental health problems, aiming to find and develop adequate prevention and promotion of programs directed towards improvement of mental health and quality of life.